Social Potection for the Harder Road Ahead : Containing the Social Costs of Lower Growth in Latin America and the Caribbean - World Bank Group (World Bank, Washington, DC, 2015)
During a decade of rapid growth, more jobs and higher wages dramatically reduced poverty and drove down historically high levels of inequality. Governments in the region complemented the gains from growth with investments in social protection policies, further reducing poverty and inequality. Countries in Latin America and the Caribbean are rightfully proud of these achievements. As the region prepares for a long period of slower growth and tighter budgets, the value of their investment in building social protection systems will grow. Social protection can help protect social gains as labor earnings and employment fall. The evidence accumulated from the region’s experience of which social protection interventions work and which do not, will be an essential resource to guide difficult policy decisions. Countries will move ahead with the long run development of their diverse social protection systems as they are able. But in the shorter run three areas of policy action will rise in priority: (i) protecting poor and vulnerable people through the lean years; (ii) finding fiscal savings in reforms to large and regressive items of social policy; and (iii) fielding labor market initiatives to support workers during a long, slack period and prepare them for economic recovery.